SEISMIC ANALYSIS OF MULTISTORIED BUILDING WITH AND WITHOUT VERTICAL MASS IRREGULARITY - RASHMI S PATIL; PROF. H S VIDYADHAR; DR. S B PATIL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The current trend NVH plays an important role while designing the BIW of automobile vehicle. Acoustic baffle is one of the important parts of a vehicle which helps in reducing the NVH of vehicle. This report gives the design of baffle for section 8 of lower end of A pillar. Previously baffle was made by pressing the expandable foam material between the two metal plates. These metal plates are replaced by a plastic carries which is made up of polyamide. These plastic carries are manufactured by using the injection molding & after that expandable foam, made of ethylene/vinyl-acetate copolymers (EVA) is overmold on the plastic carrier. Selection of expandable foam material various testing need to be carried out like, temperature storage stability (before & after expansion), adhesion, mechanical behavior, expansion behavior, chemical &corrosion stability. Also snapping feature design provides the advantage of using the same baffle for both right hand side & left hand side of pillar. By using this baffle noise level can be reduced up to 15db. When BIW goes into the electro coat baking oven, the sealing material is being heated to a temperature in the range of the activation temperature. The heat expandable material is sealing the peripheral gap between the carrier and the inner side of the cavity walls. After the expansion of foam NVH test will be carried out at vehicle level to compare the results. The use of expandable foam baffles with plastic material as a carrier replaces the use of metal carrier & thereby reducing the complexity, cost, reduced weight & reduced assembly operations. As the metal part is avoided there is no possibility of rusting of pillars or baffle. Also the main advantage is, the injection molding process gives the consistency in the part & therefore the foam reaches corner sealing with guided expansion.